The Political Impact of Social Insecurity in France - Mayer, Nonna (PARTECIPAZIONE E CONFLITTO, 2019)
Drawing on the case of France during the 2017 presidential election, which was marked by the victory of the centrist Emmanuel Macron and the surge of the populist radical right (Marine Le Pen) and left (Jean-Luc Mélenchon), this paper analyses the impact of social insecurity on voting, using a multidimensional indicator of "precariousness" that combines measures of economic hardship and social and cultural isolation. On the basis of the 2017 French Election Study, a series of logistic regressions estimate the impact of precariousness on individual vote choice (including abstention) in both rounds, controlling for socio-demographic and attitudinal variables. Precariousness mainly has a strong negative impact on turnout, silencing the most deprived. Among those who vote, it has a strong negative impact on support for Emmanuel Macron. It also has a positive impact on support for the populist radical right and, to a lesser extent, on support for the populist radical left when controlling for socio-demographic variables. But this effect practically disappears after controlling for attitudes. Social insecurity does not necessarily breed populism. Ideological divisions make the difference, especially attitudes towards the European Union, immigration, and the left-right divide.